All Questions Topic List
Trigonometry Questions
Previous in All Question Next in All Question
Previous in Trigonometry Next in Trigonometry
Question Number 43266 by gunawan last updated on 09/Sep/18
cos3x+cos−3x=0sin2x+cos2x=...
Answered by tanmay.chaudhury50@gmail.com last updated on 09/Sep/18
t=cosx+isinx=eix1t=cosx−isinx=e−ixt+1t=2cosx(t+1t)3=23cos3x123(t+1t)3=cos3xnow123(t+1t)3+1123×(t+1t)3=0{123(t+1t)3}2+1=0126(t+1t)6+1=0now(t+1t)6+26=0(t+1t)6=26i6t+1t=2i2cosx=2icosx=isin2x+cos2x=2sinx.cosx+2cos2x−1=21−cos2xcosx+2cos2x−1=21−i2×i+2i2−1=22×i+2(−1)−1=−3+22it
Terms of Service
Privacy Policy
Contact: info@tinkutara.com